Early childhood caries: a bibliometric analysis - Fadhlina, Anis (2023)
Introduction: It is estimated that 48% of children globally and over 70% of those in Malaysia suffer from early childhood caries (ECC). ECC leads to losing permanent teeth at a very early age, malnutrition, and lower quality of life.